Management and Organization Review Special Issue 'Business Model Innovation in Transforming Economies'. (28th December 2017) - Volberda, Henk; Mihalache, Oli; Fey, Carl; Lewin, Arie Y.
Abstract : Transforming economies such as the BRIC countries – Ex-Soviet Republics, or Eastern European countries – share national aspirations of becoming innovation economies. These aspirations have stimulated a push for entrepreneurship and experimentation with new ways of doing things. This has created a fascinating context for research on business model innovation, relating to the way incumbent firms adapt their business models or come up with entirely new models. Similarly, new business models may be originated by start-up companies that often are challenging and leapfrogging the 'tired' old business models or simply invent new ones. However, research that specifically explores indigenous business model innovation in the context of these transforming economies is still in its early stages. The MOR special issue on ' Business Model Innovation in Transforming Economies ' aims to address this gap by soliciting research uncovering successful new business models that is indigenous to these economies, as they transition to becoming innovation economies themselves and contribute to strategy and management theory development.